The Effect of different preservation methods on the vitamin C and total phenolic content in okra (Abelmoschus esculentus L.) during storage Period: تأثير طرائق الحفظ والتخزين على الخصائص الكيميائية في البامياء - رجوب, سالي (Submission and Review of Research -Biological Sciences Series, 2025)
In this research, the okra samples were washed and boiled with hot water at 85 ° C for 2 minutes with the addition of salt by (0.5%) and then exposed to different preservation methods: natural drying methods, drying in the hot air oven at a temperature of 55 ° C and freezing at a temperature (-16, -20 ° C), and kept for 6 months, antioxidants (vitamin C, total phenols) were identified at different periods 0,2,4,6 months. The results of this research showed that at the end of the storage period (6 months), the freezing method maintained a high content of phenols (2.96 ± 0.04g ̸ 100g), while the total content of phenols decreased when preserving natural drying (1.33 ± 0.03g ̸ 100g) and oven drying (1.09 ± 0.03g ̸ 100g), and thus was the most effective way to maintain these vital compounds. The content of vitamin C also changed similar to the change of phenols, as the results show that the two methods of drying and natural drying have caused a significant decrease (P<0.05) in the content of vitamin C compared to the freezing treatment (3.13 ± 0.04, 3.48 ± 0.11,16.5 ± 0.07 mg ̸ 100g respectively). Consequently, our research concluded that boiled and frozen okra leads to better results in preserving plant chemical properties over time compared to other methods.